The research and application an X-pinch on compact pulsed power generators - Artyomov, Anton P.; Chaikovsky, Stanislav A.; Oreshkin, Vladimir I.; Ratakhin, Nikolay A.; Fedunin, Anatoly V.; Lavrinovich, Ivan V.; Rousskikh, Alexander G.; Zhigalin, Alexander S. (IEEE conference record-abstracts - IEEE International Conference on Plasma Science, 2015)
Summary form only given. Since 2006, researches of the X-pinch dynamics have been carried out at the Institute of High Current Electronics (Tomsk, Russia) on compact pulsed power generators (100-250 kA, 110-180 ns) of our own design. Considerable amount of the experimental data was accumulated during these years. It was shown experimentally that at the region of initial cross point of the X-pinch wires a plasma neck with a length of 200-300 microns develops, where a small scale constriction is formed immediately before an X-ray burst producing a "hot spot" 1 . The "hot spot" size does not exceed 2.5 microns in a spectral range of quantum energies hv > 3 keV for X-pinches consisting of two-four thin Mo or W wires. The full width at half maximum (FWHM) of an x-ray pulse for such X-pinches is less than 2 ns. The measured length of the plasma neck coincides well with that resulting from the numerical simulations of the X-pinch dynamics 2 . The compact pulsed power generators with X-pinch loads have been tested as a diagnostic tool of the ultrafast physical processes in different researches (electrical explosions of wires and foils, wire array implosions, etc.) 3 ' 4 . On the base of these generators, a synchronized multiframe complex for radiography with a nanosecond exposure time has been created and tested in the experiments 5 .